WHO IS GUILTY? INVESTIGATING THE CAUSE OF DAMAGED PRODUCTS IN SMALL-LOCAL RETAILER - Yoga, I Made Sindhu; I Gede Wirajati Merta (Universitas Pendidikan Nasional, 2020)
The aim of this study is to find out who is responsible and which activities are often become the main problem of the damage products in local-retailer by following the distribution, supply chain, and value chain process. The motivation of this research comes up with the issue that the damaged product often occurs, especially in retail companies that sell products directly to the end users. The phenomenon of damaged products is interesting to study because when damaged goods failed to be sold, then it will be a loss for the company. Using semi-structural interview techniques for information gathering, followed by conducted in-depth interviews related to the issue, this study shows that the warehouse or retail staff who placing, delivering and displaying goods, are prone as the actors of the damaged product. Keywords: damaged products, distribution, supply chain, value chain